TINJAUAN PENERAPAN E-COURT DI PENGADILAN NEGERI YOGYAKARTA BERDASARKAN TEORI HUKUM LAWRENCE M. FRIEDMAN - Muhammad Rafif; Zakki Adlhiyati (Verstek, 2023)
This article analyzes the application of e-Court in civil proceedings in the Yogyakarta State Court of Class IA. The purpose of this article is to learn more deeply how the Yogyakarta State Court of Class IA uses e-Court in civil proceedings. The results of the analysis proved that the legal structure of the Yogyakarta Court has been well implemented, with legal jurisdiction over 14 districts located in Yogyakarta City, the capital of Yogyakarta Province. The legal substance of the Yogyakarta Court has been well developed, based on the updated Rules of the Supreme Court No. 2022 by the Supreme Court. 1 In 2019 on the Electronic Administration of Cases and Trials in Courts, the regulation indicates that the regulations have already supplemented what is the shortcomings of this e-court system. Legal culture in Yogyakarta State Court has also been well implemented, marked by the presence of supporting applications such as SIPP that serve to provide information related to administrative matters.Keywords: Civil Law; Civil Procedure; E-Court; District Court